2010
DOI: 10.1111/j.1478-3231.2009.02181.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver injury upregulates microRNA-491-5p in mice, and its overexpression sensitizes Hep G2 cells for tumour necrosis factor-α-induced apoptosis

Abstract: One of the miRNAs that is associated with the acute liver injury mouse model, miRNA-491_5p, sensitizes Hep G2 cells for TNF-alpha-induced apoptosis, at least in part, by inhibiting AFP, hsp-90 and NF-kappaB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…miRNA Isolation, Labeling, Purification, and Microarray miRNA isolation, labeling, and purification were performed as we reported previously (12). Hybridized miRNA slides were scanned with a Genepix 4000B scanner (Agilent Technologies Inc., Santa Clara, CA) (12).…”
Section: Ssglt and 50% Ph In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA Isolation, Labeling, Purification, and Microarray miRNA isolation, labeling, and purification were performed as we reported previously (12). Hybridized miRNA slides were scanned with a Genepix 4000B scanner (Agilent Technologies Inc., Santa Clara, CA) (12).…”
Section: Ssglt and 50% Ph In Ratsmentioning
confidence: 99%
“…The administration of nucleic acid-modified oligonucleotide complementary to miR_122 led to long-lasting hepatitis C virus suppression in infected chimpanzees without resistance (10). In previous studies, we have characterized the signatures of miRNAs in acute liver injury and hepatic fibrosis and defined the molecular targets of significantly increased or suppressed miRNAs in these processes (11,12). To our knowledge, no information regarding whether miRNAs participate in modulation of liver growth in LDLT is available in the literature.…”
mentioning
confidence: 99%
“…97 These and other studies demonstrate that miRs regulate death receptor-mediated hepatocytes apoptosis in ALF. 98,99 Serum miRs that regulate hepatic apoptotic pathways may be shed into the circulation and reflect the degree of hepatic cell death could serve as reporters for progression of ALF.…”
Section: Acute Liver Failure (Alf)mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a family of endogenous, noncoding, small single stranded RNAs (21-25 nucleotides) that regulate the gene expression at post-transcriptional levels (Venugopal et al, 2009;Yoon et al, 2010). miRNAs bind to the target sequences by partial or complete binding to the 3' untranslated region (UTR) of their target mRNAs, and thereby mediate mRNA degradation or translational inhibition, which depends on the degree of complementarity between miRNAs and their targets (Carthew, 2006).…”
Section: Micrornasmentioning
confidence: 99%
“…Several study reports have been showed that antibodies linked to NP can detect or target cells with high specificity (Yang et al, 2007). In our recent study, we have used gold nanoparticles (AuNP) of a small size (10 nm) coated with streptavidin (SA) for conjugation of molecules to create a nanoimmunogene conjugate (Yoon et al, 2010). This conjugates includes an apoptosis-inducing miRNA (miRNA-491), breast cancer targeting MAb, and quantum dots to target breast cancer selectively and to induce apoptosis (Natarajan et al, 2009).…”
Section: Nanoparticles In Breast Cancer Translational Researchmentioning
confidence: 99%